RETRACTED: Pengaruh Promosi Dan Penetapan Harga Terhadap Keputusan Pembelian Produk Cendo - Arif Siaha Widodo; Surti Wardani (Jurnal Pemasaran Kompetitif, 2020)
RETRACTED : Artikel ini telah di RETRAKSI karena data yang disajikan tidak sesaui dengan fakta sebenrnya.Abstract. This study aims to determine the effect of promotion on the purchase decision of PT Penta Valent Jakarta products, to find out the effect of price setting on the "purchase decision" of cendo product PT Penta Valent Jakarta" and to determine the silmultaneous effect  of "promotion and price determination on the purcahse decision of cendo product  "PT Penta Valent Jakarta". The "analysis method" is used multiple linear regression test, t test and F test. The population are all the consumers who use cendo product  PT Penta Valent Jakarta and the sample size are "100 respondents". The results show a positive effect of promotion on the "purchase decision" of cendo PT Penta Valent Jakarta with a coefficient value of "equal to" 0.519 and  t value > t table or 5.884> 1,660. Pricing has a positive effect on purchasing decisions with a coefficient value obtained "of 0.327" and  t valuet > t table or 8.007 > 1,660. Promotion and price simultaneously have a positive and significant effect on purchasing decisions for cendo product PT Penta Valent Jakarta, with the equation Y = 7.210 + 0.519 X1 + 0.327 X2 and F value > F table that is 60,369> 3,090.  Keywords:" Promotion; "Pricing; Purchase Decisions